2018
DOI: 10.3174/ajnr.a5693
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Cerebral Perfusion Changes in Children with Migraine with Aura Mimicking Stroke

Abstract: Hemiplegic migraine is a common cause of acute brain attack in pediatrics. MR imaging sequences useful in differentiating hemiplegic migraine from other entities include arterial spin-labeling, SWI, MRA, and DWI. There has been limited exploration on the simultaneous use of these sequences in pediatrics. We present 12 pediatric patients with acute hemiplegic migraine or migraine with aura who underwent MR imaging within 12 hours of symptom onset. Quantitative and qualitative analyses were performed on arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…We found a significant association between headache side and the brain hemisphere that visually harboured more PFV. Previous studies have shown that migraine with aura is often associated with unilateral changes in cerebral perfusion which may provoke headache symptoms [7,13]. We believe that the brain hemisphere most affected by these hemodynamic changes on average show more PFV [21] and may therefore represent the clinically affected side.…”
Section: Plos Onementioning
confidence: 86%
See 1 more Smart Citation
“…We found a significant association between headache side and the brain hemisphere that visually harboured more PFV. Previous studies have shown that migraine with aura is often associated with unilateral changes in cerebral perfusion which may provoke headache symptoms [7,13]. We believe that the brain hemisphere most affected by these hemodynamic changes on average show more PFV [21] and may therefore represent the clinically affected side.…”
Section: Plos Onementioning
confidence: 86%
“…We found a negative correlation between time elapsed and the CDH volume. The most likely explanation for this is the time-dependent decrease of deoxygenation of venous cerebral blood throughout the course of MwA, with decreasing conspicuity of the venous vasculature on SWI over time [13,14].…”
Section: Plos Onementioning
confidence: 99%
“…In 28.6%, it occurs in the rest of the vascular territories [ 2 ], and they can be observed generally during the aura [ 4 ] and in fewer cases during the progression of the headache. The range of time goes from 11 h [ 5 ] up to 12 days, but in all cases, the changes were reversible [ 6 ]. In these latter circumstances, hypoperfusion is regional [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 One case series of pediatric patients has demonstrated that among ASL, susceptibility weighted imaging, MRA, and diffusion weighted imaging, ASL is the most sensitive in detecting hemiplegic migraine. 5 Therefore, ASL may have utility in differentiating between hemiplegic migraine and stroke. As regards perfusion abnormality, the same study used ASL to demonstrate that initial hypoperfusion in migraine was followed by rebound hyperperfusion.…”
Section: Figmentioning
confidence: 99%
“…As regards perfusion abnormality, the same study used ASL to demonstrate that initial hypoperfusion in migraine was followed by rebound hyperperfusion. 5 Thus, the discrepancy in whether migraine is correlated with hypoperfusion or hyperperfusion may instead be explained by the chronicity of perfusion changes in migraine presentation, as demonstrated by ASL imaging.…”
Section: Figmentioning
confidence: 99%